Analysis of the Application of PSAK 24 Revised 2013-Accounting for Employee Benefits Referring to Law Number 13 at PT. ABC (Project Unit Credit Method) - Albart, Nicko; Herru, Herru (Yayasan Riset dan Pengembangan Intelektual, 2024)
Each entity has the obligation to present financial statements that accord with the Statement of Financial Accounting Standards (PSAK) and the relevant rules. This will affect the external auditors opinions and the accounting division performances. This research was to analyse the effects of the application of the PSAK 24 Revised 2013 on the employee benefits in the PT ABC financial statements. Case study on PT. ABC was conducted using a qualitative analysis with data triangulation methods. This research was carried out by conducting interviews and document analyses. the researcher analysed the effects of the application of the PSAK 24 Revised 2013 on the financial statements (balance sheet and profit and loss) of PT. ABC. The difference appearing from the revision was the recognition of actuarial loss gains which were entirely recognized in the other comprehensive income, changes in the calculation component to measure the past service costs, net costs, and liabilities. The results of this research indicated that PT. ABC has made adjustments due to the implementation of the PSAK 24 Revised 2013. PT ABC has also retrospectively reviewed the financial statements for the period of 1 January 2023 and 31 December 2023.